Analysis of Leadership Styles in Building Social Harmony in Rural Communities: A Systematic Review - Sadria, Ade; Sulistiyo, Urip; Firman, Firman (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This systematic review integrates findings from studies on leadership styles transformational, paternalistic, and participative and their influence on social harmony and community development within rural Indonesian contexts. Following the PRISMA methodology, 150 pertinent articles were initially identified, with 11 studies ultimately selected for rigorous in-depth analysis. The results reveal that transformational leadership fosters innovation and collective action, substantially enhancing social cohesion and community participation. However, its efficacy is often undermined by entrenched socio-cultural hierarchies and limited educational infrastructure in rural settings. Paternalistic leadership, while adept at maintaining social stability and moral order, constrains flexibility and impedes innovation, rendering it less adaptable to the exigencies of modernization. Participative leadership emphasizes inclusivity and shared decision-making, thereby strengthening community involvement, but it remains hampered by resource scarcity and temporal constraints. A recurring theme throughout the analysis highlights the necessity of aligning leadership practices with local cultural norms to build community trust and optimize the success of development initiatives. This review ultimately underscores the imperative for culturally attuned leadership that not only preserves indigenous wisdom but also navigates the challenges of modernization, fostering sustainable development in rural communities.